TRICUSPID VALVE INSUFFICIENCY IN RECIPIENTS WITH TRANSPLANTED HEART - V. I. Orlov; R. Sh. Saitgareev; A. O. Shevchenko (Вестник трансплантологии и искусственных органов)
Tricuspid valve insufﬁ ciency is one of the most common variants of valve pathology of transplanted heart. The review is sanctiﬁ ed to the analysis of modern looks to on causes, potentially inﬂ uencing on development of tricuspid valve insufﬁ ciency of transplanted heart, and also methods sent to declines risk his development.